2017
DOI: 10.1007/s11103-017-0647-z
|View full text |Cite
|
Sign up to set email alerts
|

The MEDIATOR genes MED12 and MED13 control Arabidopsis root system configuration influencing sugar and auxin responses

Abstract: Arabidopsis med12 and med13 mutants exhibit shoot and root phenotypes related to an altered auxin homeostasis. Sucrose supplementation reactivates both cell division and elongation in primary roots as well as auxin-responsive and stem cell niche gene expression in these mutants. An analysis of primary root growth of WT, med12, aux1-7 and med12 aux1 single and double mutants in response to sucrose and/or N-1-naphthylphthalamic acid (NPA) placed MED12 upstream of auxin transport for the sugar modulation of root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 54 publications
1
26
1
Order By: Relevance
“…With this aim, we analyzed the effects of leaf applied sucrose on root development, according to Raya‐González et al . (). In WT and med18‐1 seedlings, sucrose supplied to the shoot increased lateral root formation (Figure S4), suggesting that vascular transport was not compromised by the lack of a functional MED18.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…With this aim, we analyzed the effects of leaf applied sucrose on root development, according to Raya‐González et al . (). In WT and med18‐1 seedlings, sucrose supplied to the shoot increased lateral root formation (Figure S4), suggesting that vascular transport was not compromised by the lack of a functional MED18.…”
Section: Resultsmentioning
confidence: 97%
“…Because cell death in med18 mutants is specific of initial cells of a tissue that later differentiates into vasculature, we assessed whether the phloem transport could be affected in med18-1 roots. With this aim, we analyzed the effects of leaf applied sucrose on root development, according to Raya-Gonz alez et al (2017). In WT and med18-1 seedlings, sucrose supplied to the shoot increased lateral root formation (Figure S4), suggesting that vascular transport was not compromised by the lack of a functional MED18.…”
Section: Med18 Mutation Triggers Cell Death In the Root Apical Meristemmentioning
confidence: 99%
See 1 more Smart Citation
“…MED25, part of the tail module) (Muñoz‐Parra et al ., ) although the functions of some others (e.g. MED12 and MED13, components of the kinase module) appear to overlap (Raya‐González et al ., ). It might be expected that knockout mutations in any one component would yield similar phenotypes, but that is not the case.…”
mentioning
confidence: 97%
“…They examined the effect of light because they previously showed that the phenotypes of med12 and med13 seedlings, which have very short roots, were corrected when the medium was supplemented with sucrose (Raya‐González et al ., ). Sucrose did not correct the med18 phenotype.…”
mentioning
confidence: 97%